1981
DOI: 10.1079/bjn19810097
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the absorption of iron from Fe(III)EDTA

Abstract: 1. The modification of iron absorption from Fe(III)EDTA by agents known to promote or inhibit absorption was examined in 101 volunteer multiparous Indian women. Fe absorption from Fe(III)EDTA was compared with absorption of intrinsic food Fe in a further twenty-eight subjects. Finally the urinary excretion of radio-Fe after oral administration of59Fe(III)EDTA was studied in twenty-four subjects and evidence of intraluminal exchange of Fe was examined.2. Fe absorption from maize porridge fortified with Fe(III)E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 19 publications
4
36
1
Order By: Relevance
“…The high bioavailability of iron from NaFe-EDTA has been repeatedly reported, showing that iron absorption from this compound is at least 2 times higher than absorption from FeSO 4 , depending on the meal [2,9,10,16,31,32]. Iron uptake results from NaFe-EDTA by Caco-2 cells were unexpectedly low, since this model has been extensively validated regarding iron uptake.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…The high bioavailability of iron from NaFe-EDTA has been repeatedly reported, showing that iron absorption from this compound is at least 2 times higher than absorption from FeSO 4 , depending on the meal [2,9,10,16,31,32]. Iron uptake results from NaFe-EDTA by Caco-2 cells were unexpectedly low, since this model has been extensively validated regarding iron uptake.…”
Section: Discussionmentioning
confidence: 79%
“…It has been reported that the use of NaFe-EDTA does not represent any additional benefit over other iron compounds in meals of high bioavailability [1]. Iron absorption studies in humans [10], show that ascorbic acid enhanced iron absorption from a maize porridge when a 1:6 iron:ascorbic acid molar ratio was used. We found that a 1:2 iron:ascorbic acid molar ratio, significantly enhanced iron uptake by Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations